Building given beautiful life - Ferrendelli, Betta (Raton Range Raton, NM, 1991)
This article is talking about the renovations done on the Cook Building located on Historic First Street.
Newspaper article + Photograph of Hattie Sloan
Master list item #: 1
File location is in the Raton file Cabinet
Keywords: Sloan, Hattie -- Owner; Naylor, Cathy; Jeffryes, Randy -- Contractor; Heirloom Shop; Historic Preservation Office -- Santa Fe, New Mexico; Jeffryes Builders; Cook Building; Building Restorations; History Buildings; Old Buildings; Building Renovations; First Street and Cook Avenue; Raton, New Mexico